Modified Multiwalled Carbon Nanotubes for Treatment of Some Organic Dyes in Wastewater - M. I. Mohammed; Adnan A. Abdul Razak; Dhiyaa A. Hussein Al-Timimi (Advances in Materials Science and Engineering)
In Iraq, a large quantity of basic orange and methyl violet dyes contaminated wastewater from textile industries is discharged into Tigris River. So the aim of this work is to found an efficient and fast technique that can be applied directly for removal of such dyes from the wastewater before discharging into river. Accordingly, CNTs as a new approach prepared by CCVD technique were purified, functionalized, and used as adsorption material to remove dyes from wastewater. The effect of pH, contact time, CNTs dosage, and dyes concentration on removal of pollutants was studied. The removal percentage of both dyes was proportional to the contact time, CNTs dosage, and pH and inversely proportional to the dyes concentration. The results show that the equilibrium time was 20 and 30 min for basic orange and methyl violet dyes, respectively, and the maximum removal percentage for all dyes concentrations was at pH = 8.5 and CNTs dosage of 0.25 g/L and 0.3 g/L for methyl violet and basic orange dye, respectively. The adsorption isotherm shows that the correlation coefficient of Freundlich model was higher than Langmuir model for both dyes, indicating that the Freundlich model is more appropriate to describe the adsorption characteristics of organic pollutants.